Destructive forms of leadership: The effects of abusive supervision and incivility on employee health and safety. Issue 8 (24th August 2018) - Mullen, Jane; Fiset, John; Rhéaume, Ann
Abstract : Purpose: The purpose of this paper is to examine the relationship between abusive supervision and employee health and safety outcomes in Study 1 and to examine the effect of inconsistent leadership, operationalized as the interaction between transformational leadership and supervisor incivility, on employee safety participation in Study 2. Design/methodology/approach: In Study 1, survey data were gathered from n =145 healthcare workers. In Study 2, survey data were gathered from n =177 nurses. Findings: A partially mediated structural model was estimated in Study 1 and the results show that the model provided a good fit to the data χ 2 (1)=1.27, p =0.23. Abusive supervision predicted safety climate ( β =−0.41, p <0.01) and psychological health ( β =−0.27, p <0.01). Safety climate, in turn, predicted psychological health ( β = 0.40, p <0.01) and safety participation ( β = 0.37, p <0.01). Study 2: moderated regression analysis showed that inconsistent leadership significantly predicted employee safety participation, F (5, 144)=4.46, p <0.01. Originality/value: Theoretical and practical implications for creating psychologically healthy workplaces through interventions aimed at improving leader effectiveness are discussed.